Розвиток технології PLC в сучасних умовах та забезпечення безпеки споживача - Холод, Л. М.; Сабурова, С. О. (ХНУРЕ, 2021)
The article considers the directions of using PLC technology in modern conditions and issues of safety of human life during its use. The use of PLC technology in the market of automated energy metering systems has great prospects. PLC technology has opened the way to create automated information and measurement systems. The PLC technology is based on three key lines: for organizing a local system for a Narrowband and an office (BPL), organizing a system "Smart Dim" / "Smart Speeches" (Narrowband PLC and BPL) as well, as for securing automatic collection of information from electric power lines (Narrowband PLC).
Keywords: Розвиток тезнологій; PLC